2010
DOI: 10.1007/s10533-010-9430-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and dissolved organic matter on the abundance of nirK and nirS denitrifiers in spruce forest soil

Abstract: Acid N depositions in the Bohemian Forest during the second half of the last century caused enormous soil acidification which led to the leaching of essential nutrients including nitrates. We investigated the effect of dissolved organic matter (DOM) and pH on the abundance of 16S RDNA, nirK and nirS gene copies in four spruce forest sites. Soil samples for molecular based quantification (qPCR) were taken from the organic litter and humus layers. The amounts of dissolved organic carbon (DOC) and dissolved nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
64
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(75 citation statements)
references
References 45 publications
9
64
2
Order By: Relevance
“…Despite the fact that 16 years of reduced N deposition in spruce forest soil increased NH 4 + availability but did not affect denitrification genes ), Levy-Booth et al (2014) still pointed out that the abundance of certain denitrification genes (napA, nirS, nirK, and nosZ) in forest soils will increase with increasing total N and NH 4 + concentrations through exogenous N input if soil pH, moisture, and organic C favor or facilitate denitrification. In a highly acidic spruce forest soil, Bárta et al (2010) found that there were exponential correlations between the amount of nirK denitrifiers and DOC and pH, showing two important threshold values being 4.8 mol kg −1 and 5, respectively, and below these two values, the amount of nirK denitrifiers decreased rapidly. Therefore, decreased soil pH and C availability may mitigate the stimulation of N deposition and fertilization on denitrification in forest ecosystems (Šimek et al 2002), which may provide explanations for the reversed trends in denitrification (N 2 O emission) of forest soils over time under fertilization (Aronson and Allison 2012;Bengtsson and Bergwall 2000).…”
Section: Denitrification and N 2 O Emissionmentioning
confidence: 97%
See 3 more Smart Citations
“…Despite the fact that 16 years of reduced N deposition in spruce forest soil increased NH 4 + availability but did not affect denitrification genes ), Levy-Booth et al (2014) still pointed out that the abundance of certain denitrification genes (napA, nirS, nirK, and nosZ) in forest soils will increase with increasing total N and NH 4 + concentrations through exogenous N input if soil pH, moisture, and organic C favor or facilitate denitrification. In a highly acidic spruce forest soil, Bárta et al (2010) found that there were exponential correlations between the amount of nirK denitrifiers and DOC and pH, showing two important threshold values being 4.8 mol kg −1 and 5, respectively, and below these two values, the amount of nirK denitrifiers decreased rapidly. Therefore, decreased soil pH and C availability may mitigate the stimulation of N deposition and fertilization on denitrification in forest ecosystems (Šimek et al 2002), which may provide explanations for the reversed trends in denitrification (N 2 O emission) of forest soils over time under fertilization (Aronson and Allison 2012;Bengtsson and Bergwall 2000).…”
Section: Denitrification and N 2 O Emissionmentioning
confidence: 97%
“…In addition, they found that the richness and diversity of genes involved in the decomposition of starch (~12 %), hemicellulose (~16 %), cellulose (~16 %), chitin (~15 %), and lignin (~16 %) were also significantly reduced by experimental N deposition. Lots of studies have proven that increased N deposition to forest ecosystems has led to soil acidification (Fluckiger and Braun 1998;, which may also affect the activities of soil microbes and C availability (Bárta et al 2010;Fang et al 2004). For instance, in a highly acidic spruce forest soil, the amounts of dissolved organic C (DOC) and dissolved N were found to be very low (Bárta et al 2010).…”
Section: N Mineralizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Copy numbers of nirS outnumbered nirK by 2 to 3 orders of magnitude in both acidic peat soils ( Table 5), indicating that nirS-rather than nirK-type denitrifiers were associated with denitrification in acidic peat soils. Indeed, nirS abundance in spruce forest soil was positively correlated with decreasing pH from 6.1 to 3.7, whereas nirK abundance was negatively correlated (Barta et al, 2010). Such data suggest that low pH and high moisture contents might favor nirS-type rather than nirK-type denitrifiers in acidic peat soils and highlight differences in detected nitrite reductase gene containing denitrifier communities of cryoturbated and unturbated peat soils.…”
Section: Discussionmentioning
confidence: 84%